2007
DOI: 10.1029/2007jd008528
|View full text |Cite
|
Sign up to set email alerts
|

Midlatitude tropospheric ozone columns derived from the Aura Ozone Monitoring Instrument and Microwave Limb Sounder measurements

Abstract: [1] Tropospheric ozone columns derived from differences between the Dutch-Finnish Aura Ozone Monitoring Instrument (OMI) measurements of the total atmospheric ozone column and the Aura Microwave Limb Sounder (MLS) measurements of stratospheric ozone columns are discussed. Because the measurements by these two instruments are not spatially coincident, interpolation techniques, with emphasis on mapping the stratospheric columns in space and time using the relationships between lower stratospheric ozone and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Different techniques have been recently proposed to monitor tropospheric ozone from satellites including OMI: see, e.g. the methods proposed by Ziemke et al (2006a,b); Yang et al (2007); Schoeberl et al (2007); Stajner et al (2008); Liu et al (2010b). Three major techniques exist within this field.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been recently proposed to monitor tropospheric ozone from satellites including OMI: see, e.g. the methods proposed by Ziemke et al (2006a,b); Yang et al (2007); Schoeberl et al (2007); Stajner et al (2008); Liu et al (2010b). Three major techniques exist within this field.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the biases between MLS and the operational observations have degraded the ozone analyses below 215 hPa. Recently, Ziemke et al [2006] and Yang et al [2007] used MLS ozone data to determine the tropospheric ozone columns together with the total ozone columns from the Aura Ozone Monitoring Instrument (OMI). Their results encourage us in the future to further explore the way to improve the tropospheric ozone analyses from the combined assimilation of the more accurate version 2.2 MLS data and the operational ozone observations through careful bias correction and observation selection such as excluding SBUV/2 data at certain layers.…”
Section: Resultsmentioning
confidence: 99%
“…It is also found that version 1.51 has slightly more ozone in the lower stratosphere (by a few percent) and less ozone in the upper stratosphere (by up to 10% at 1 hPa), when compared to the new (version 2.2) MLS data set [Froidevaux et al, 2008]. Moreover, a recent study by Yang et al [2007] shows that the stratospheric ozone columns of the version 1.51 data set are higher than SAGE II observations by about 3 Dobson units (DU). In the experiment, we only use version 1.51 data flagged as good.…”
Section: Assimilated Ozone Observationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the late 1980s, TCO data have been derived by subtracting concurrent measurements of stratospheric column ozone (SCO) from total column ozone (Fishman et al 1986;Fishman and Larsen 1987;Fishman et al 1990), and these were further improved afterward (Fishman et al 2003;Chandra et al 2003). Most recently, several studies derived TCO from Aura Microwave Limb Sounder (MLS) SCO and Ozone Monitoring Experiment (OMI) measurements by using spatial interpolation (Ziemke et al 2006), trajectory mapping (Schoeberl et al 2007), potential vorticity (Yang et al 2007), and data assimilation (Stajner et al 2008) to improve the spatial coverage of MLS data. Alternatively, Liu et al (2005Liu et al ( , 2006 derived TCO directly from the spectra obtained by the Global Ozone Monitoring Experiment (GOME).…”
Section: Introductionmentioning
confidence: 99%